HUBUNGAN KEBERSIHAN GIGI DAN MULUT DENGAN KONDISI GINGIVA PADA SISWA SMP - Eka Sukanti; Eriyati Eriyati; Aflinda Yenti; Muhammad Faisal; Triana Dewi (Menara Medika, 2024)
Poor oral and dental hygiene can cause plaque to build up on the surface of the teeth. Plaque buildup that is not cleaned will harden and disrupt the condition of the gingiva, resulting in inflammation of the gingiva. The aim of this research was to determine the relationship between dental and oral hygiene and gingival conditions in students at SMP Negeri 2 Baso, Agam Regency. This research uses analytical methods. Research subjects were taken using a saturated sampling technique. Data collection was carried out by examining the Plaque Index (IP) and Gingival Index (GI), with data analysis using the "Spearman correlation" statistical test. The results of the study showed that there was a significant relationship between dental and oral hygiene and gingival conditions. The results of the "Spearman correlation" statistical test obtained a p-value of 0.0180.05. Most students had a Plaque Index with moderate criteria and mild inflammation criteria. It is recommended that students pay more attention to oral and dental hygiene, such as brushing their teeth twice a day, namely in the morning after breakfast and at night before bed, consuming fruit and vegetables, gargling with antiseptic and using dental floss or dental floss so that the condition of the gingiva is well maintained so that they can prevent inflammation of the gingiva.